Multiple structural proteins are required for both transcriptional activation and negative autoregulation of Caulobacter crescentus flagellar genes. - Ramakrishnan, G (1994)
The periodic and sequential expression of flagellar (fla) genes in the Caulobacter crescentus cell cycle depends on their organization into levels I to IV of a regulatory hierarchy in which genes at the top of the hierarchy are expressed early in the cell cycle and are required for the later expression of genes below them. In these studies, we have examined the regulatory role of level II fliF operon, which is located near the top of the hierarchy. The last gene in the fliF operon, flbD, encodes a transcriptional factor required for activation of sigma 54-dependent promoters at levels III and IV and negative autoregulation of the level II fliF promoter. We have physically mapped the fliF operon, identified four new genes in the transcription unit, and determined that the organization of these genes is 5'-fliF-fliG-flbE-fliN-flbD-3'. Three of the genes encode homologs of the MS ring protein (FliF) and two switch proteins (FliG and FliN) of enteric bacteria, and the fourth encodes a predicted protein (FlbE) without obvious similarities to known bacterial proteins. We have introduced nonpolar mutations in each of the open reading frames and shown that all of the newly identified genes (fliF, fliG, flbE, and fliN) are required in addition to flbD for activation of the sigma 54-dependent flgK and flbG promoters at level III. In contrast, fliF, fliG, and flbE, but not fliN, are required in addition to flbD for negative autoregulation of the level II fliF promoter. The simplest interpretation of these results is that the requirements of FlbD in transcriptional activation and repression are not identical, and we speculate that FlbD function is subject to dual or overlapping controls. We also discuss the requirement of multiple structural genes for regulation of levels II and III genes and suggest that fla gene expression in C. crescentus may be coupled to two checkpoints in flagellum assembly.